2004
DOI: 10.1093/carcin/bgh325
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer chemopreventive agent,  -santalol, induces apoptotic death of human epidermoid carcinoma A431 cells via caspase activation together with dissipation of mitochondrial membrane potential and cytochrome c release

Abstract: alpha-Santalol, an active component of sandalwood oil, has been studied in detail in recent years for its skin cancer preventive efficacy in murine models of skin carcinogenesis; however, the mechanism of its efficacy is not defined. Two major biological events responsible for the clonal expansion of transformed/initiated cells into tumors are uncontrolled growth and loss of apoptotic death. Accordingly, in the present study, employing human epidermoid carcinoma A431 cells, we assessed whether alpha-santalol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Researchers like Liang et al [53] using a series of caspase inhibitors with overlapping specificities, enzyme-specific chromogenic substrates, determined that apoptosis pathway bypassed the need for activated caspase-3 and proceeded via caspase-9, -7 and -6. Lack of sole involvement of caspases in a-santalol-induced apoptosis in A431 cells was also shown by Kaur et al [54]. They showed that pre-treatment of cells with caspase-8 or -9 inhibitor, pan caspase inhibitor or cycloheximide totally blocked a-santalolcaused caspase-3 activity and cleavage, but only partially reversed apoptotic cell death which therefore indicated the involvement of both caspasedependent and independent pathways in a-santalol-caused apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…Researchers like Liang et al [53] using a series of caspase inhibitors with overlapping specificities, enzyme-specific chromogenic substrates, determined that apoptosis pathway bypassed the need for activated caspase-3 and proceeded via caspase-9, -7 and -6. Lack of sole involvement of caspases in a-santalol-induced apoptosis in A431 cells was also shown by Kaur et al [54]. They showed that pre-treatment of cells with caspase-8 or -9 inhibitor, pan caspase inhibitor or cycloheximide totally blocked a-santalolcaused caspase-3 activity and cleavage, but only partially reversed apoptotic cell death which therefore indicated the involvement of both caspasedependent and independent pathways in a-santalol-caused apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…[57] It has also been shown to act as a skin cancer chemoprotective agent. [58] It induces apoptosis in human epidermoid carcinoma A431 cells by activation of caspase 8 and 9 which in turn activate caspase 3 and are responsible for the cleavvge of the poly (ADP-ribose) polymerase. [59] It also affects the intrinsic pathway of apoptosis as it dysfunctions the mitochondria by decreasing its membrane potential which marks the release of cytochrome c into the cytosol and results into the activation of caspase and hence apoptosis.…”
Section: Bio Active Compound and Their Mode Of Actionmentioning
confidence: 99%
“…In addition to these effects of α-santalol, it induces apoptotic death of human epidermoid carcinoma A431 cells via caspases activation through both extrinsic and intrinsic pathways. [24] This study identified the apoptotic effect of α-santalol and defined the mechanism of apoptotic cascade activated by this agent in A431 cells, which might be contributing to its overall cancer preventive efficacy in mouse skin cancer models. Although α -santalol is a major component (61%) of sandalwood oil and may be a major contributor to its skin cancer chemo-preventive effects, the effects of other components of sandalwood oil could not be ruled out.…”
Section: Anti Cancerous Propertiesmentioning
confidence: 99%
“…Mechanistic studies showed an involvement of caspase-3 activation and poly (ADP-ribose) polymerase cleavage & disruption of the mitochondrial membrane potential and cytochrome-C release into the cytoso l, thereby suggesting involvement of both caspase -dependant and independent pathways. [24] www.wjpps.com…”
Section: Vol 6 Issue 8 2017 668 Soundararajan Et Al World Journalmentioning
confidence: 99%